Identification and Measurement the Extent of the Chemicals Used for Early Ripening and Preservation of Frits in the Southwestern Region of Bangladesh - Ahmed, I.; Mannan, M. A.; Ahmed, M. B. (YRU Journal of Science and Technology, 2018)
An experiment was conducted at the Horticulture Laboratory in Khulna University, Khulna, Asia Arsenic Network Laboratory, Jessore and Pesticide Analytical Laboratory, Entomology Division, BARI, Gazipur, of Bangaldesh during the period from April to July, 2011. The objectives of the study to measure and identify the harmful chemicals (Calcium Carbide, Formalin, Ethefon) used for ripening and preservation of fruits in Jsssore, Khulna and Satkhira markets. In Jessore, Khulna, and Satkhira markets, calcium carbide was found 80%, 70% and 70% mango samples and 40%, 50% and 60% banana samples, respectively. From the same markets no carbide was found in papaya samples. Each of the Jessore and Satkhira markets no carbide was found in any jackfruits but from Khulnamarket 20% jackfruits contained calcium carbide. In Jessore markets, 20% mango, 5% banana and 2% papaya samples contained formalin. In Khulna markets 25% mango, 6% banana and 3% papaya samples contained formalin residue. It was found from Satkhira markets that 15% mango and 3% banana samples contained formalin. It was revealed that in Jessore, Khulna and Satkhira markets 80-100% mango, 40-50% banana and 30-40% papaya samples contained ethefon residue. From the above results it was revealed that maximum fruits were treated with chemicals. Therefore, it can be suggested that it is important to increase awareness in consumers and steps should be taken by the government or policy makers against the adulteration of fruits.